Applying YouTube-Based Digital Folklore Content to Enhance Writing Skills - Sakrim (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study examines the use of YouTube-based digital folklore content in creative writing instruction and its contribution to students’ writing development. The study was conducted with 30 students of the Indonesian Language and Literature Education Study Program at STKIP PGRI Bangkalan who were enrolled in the Creative Writing course in the odd semester of the 2024/2025 academic year. A mixed-methods approach was employed by combining descriptive quantitative data and qualitative classroom data. Quantitative data were obtained from pre-test and post-test writing scores as well as student-response questionnaires, while qualitative data were collected through classroom observation and interviews. The findings indicate an improvement in students’ writing performance, as reflected in the increase in the mean writing score from 60 to 85. Students’ understanding of folklore content also increased from 30% to 82%. In addition, most students responded positively to the learning process, with 95% reporting that they felt comfortable learning through YouTube-based folklore content, 93% stating that the videos helped them understand the material more quickly, and 92% reporting greater participation in classroom discussion. Qualitative findings further show that the use of audiovisual folklore content supported students’ concentration, self-confidence, and ability to develop ideas in writing. These findings suggest that YouTube-based digital folklore content can function as a contextual and engaging medium for writing instruction while simultaneously strengthening students’ cultural literacy.